Disodium Phosphate Dodecahydrate Salt Hydrate-Based Approach for Thermal Energy Storage Systems - Uttam, Amarendra; Purohit, Bijoy Kumar; Le, Minh Tam; Sistlais, Venkata Subbarayudu (Journal of Technical Education Science, 2023)
Salt hydrates, classified as inorganic phase change materials, are used in thermal energy storage (TES) systems. Due to their superior properties such as higher thermal conductivity and better thermal energy storage density, non-flammability and availability in wide temperature ranges at a reasonable cost than organic PCMs, salt hydrates are preferable PCMs. Disodium phosphate dodecahydrate (Na2HPO4·12H2O) have a favourable melting point and melting enthalpy for room temperature energy storage applications but supercooling, phase segregation, formation of lower hydrates, and corrosion to storage vessels are frequent limits to its employment, just as they are for other salt hydrates. These issues are addressed using various intensification techniques such as an aqueous saturated salt solution of Na2HPO4 (both non-gel and gel-based) instead of pure salt hydrate and using suitable nucleating, and gelling agents. Further, the intensification is done via the incorporation of solution in an open cell polyurethane (PU) foam. DSC analysis of PU-based PCM composite confirmed its melting temperature and melting enthalpy at about 35oC and 167.343 J/g recommends for its applications between 30oC- 40oC. Thermal performance observation, in a model system, shows the PU-Gel based PCM to be more efficient with a temperature difference of about 10oC- 14oC for repeated thermal cycles as compared to normal PU foam and PU-Salt based PCM.